Synthesis of substituted tetrahydro-1H-xanthen-1-ones and xanthenes - Patil, M. L.; Borate, Hanumant B. (Journal of Chemical Research, 2005)
A short and an efficient methodology for the synthesis of substituted tetrahydro-1H-1-xanthenones and xanthenes is described.
Keywords: balanol; diarylmethanes; tetrahydro-1H-xanthen-1-ones; Xanthenes